2008
DOI: 10.1007/s10551-008-9866-1
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Association Between Gender and Reporting Intentions for Fraudulent Financial Reporting

Abstract: whistleblowing, gender, fraudulentreporting, anonymous reporting channel, non-anonymous reporting channel,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
97
1
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(114 citation statements)
references
References 55 publications
7
97
1
9
Order By: Relevance
“…This difference was observed for both U.S. and Spanish executives. Kaplan et al (2009) find that women have higher intentions to report fraudulent financial reporting using anonymous channels but not for non-anonymous reporting channels. Thus, these authors conclude that gender and what drives gender effects do not apparently manifest in every judgment or decision-making setting.…”
Section: Gender Beliefs and Behaviourmentioning
confidence: 65%
“…This difference was observed for both U.S. and Spanish executives. Kaplan et al (2009) find that women have higher intentions to report fraudulent financial reporting using anonymous channels but not for non-anonymous reporting channels. Thus, these authors conclude that gender and what drives gender effects do not apparently manifest in every judgment or decision-making setting.…”
Section: Gender Beliefs and Behaviourmentioning
confidence: 65%
“…Studies have also demonstrated that women are more cautious and their business judgments are more ethical (Vermeir & Van Kenhove, 2007). Kaplan, Pany, Samuels, & Zhang (2009) found women more likely to report fraudulent financial reporting.…”
Section: Women On the Boardmentioning
confidence: 99%
“…O efeito de gênero na intenção de relatar informações de fraudes contábeis aos canais de comunicação anônimo, indicam desde a propensão maior de mulheres à denúncia (Kaplan et al,2008), até a inexistência de influência de gênero, como nos casos de Ahmad, Smith e Ismail (2010) com auditores na Malásia, e Keenan (2000) em estudo com executivos em diversos países.…”
Section: Canais De Denúnciasunclassified
“…Brennan e Kelly (2007) verificaram tal efeito para amostra de auditores trainnes na Irlanda. No mesmo sentido aponta estudo de Kaplan et al (2008) e Ahmad, Smith e Ismail (2010. Os autores apontam que esta preferência pode ser relacionada à uma maior garantia da confiabilidade da informação (preservação do denunciante) e crença na realização de ações corretivas de irregularidades gerando benefícios não só para a organização como também à sociedade.…”
Section: Canais De Denúnciasunclassified
See 1 more Smart Citation